Staphylococcus aureus enterotoxin type B (SEB) and alpha-toxin induced apoptosis in KB cell line - Milad Heidari1*; Abbas Doosti1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: According to global cancer statistics, oral cancer is the 11th most prevalent cancer worldwide. Despite the availability of numerous modern treatments for oral cancer, a complete reduction of mortality rates has not been achieved. Bacterial toxins have potential applications in inducing apoptosis or targeting tumor cells for destruction. The present study aimed to investigate the impact of Staphylococcus aureus seb and α-toxin genes on apoptotic-related gene mRNA expression, as well as apoptosis induction in KB cell lines, focusing on BAX, RB, BCL-2, and BAG-1 genes. Methods: The transfection of KB cells was performed using Lipofectamine 2000 to introduce pcDNA3.1 (+)-seb, pcDNA3.1 (+)-α-toxin, or an empty pcDNA3.1 (+) plasmid. The cells were cultured in DMEM supplemented with 10% FBS and 800 mg/L of G418 to select cells containing the plasmids. Subsequently, real-time RT-PCR was performed to measure the mRNA expression levels of BAX, RB, BCL-2, and BAG-1 genes. Cell apoptosis was assessed using Annexin V/PI staining and flow cytometry. Results: The seb and α-toxin significantly alter the expression of apoptotic-related genes in the KB cell line. In transfected KB cells, there was a significant increase in the mRNA expression of BAX and RB genes and a substantial decrease in the mRNA expression of BCL-2 and BAG-1 compared to the control group. Annexin test and flow cytometry analysis revealed that seb was more effective than α-toxin in inducing apoptosis. Conclusions: The seb and α-toxin genes of S. aureus exhibit an inhibitory effect on the growth, proliferation, and invasion of oral cancer cells by modulating gene expression in the apoptotic pathway. Hence, these toxins are promising for controlling and treating human oral cancer.